PERSPECTIVE IN THE PRACTICE OF ACCOUNTANCY. - Fagerberg, Dixon (The Accounting Review, 1955)
The article discusses the ways of viewing in perspective, the practice of accountancy. The practice of accountancy can mean far more than a mere livelihood if, as far as possible, all tendencies to take a dull, prosaic, jaundiced slant on one's work are discarded and instead meaning and inspiration in professional activities are looked for. To fulfil this goal the written word in accountancy should be clearly and interestingly conveyed, striving always to make communications compact models of useful intelligence. Varied reading should be done, thus drawing on the thinking of men of other times and places, and thereby enlarging one's own horizons and ventilating minds. Teaching, in the broadest sense, should mean creating true illumination by explaining principles. One should observe more alertly and broadly explore his professional environment, and then apply this chosen science, so that all may better adapt themselves to their limitations and likewise to their highest potentialities.